Chemotaxonomical Study of Some Species Belonging to the Genus Scabiosa l. (Dipsacaceae) in Iraq - Khazal Dh. Wadi Al-Jibouri (Journal of Global Pharma Technology, 2016)
The current study is a comparative chemotaxonomical study of five species species belonging to the genus Scabiosa L. from Dipsacaceae (Caprifoliaceae) ,wildly grown in Iraq which are S.palaestina L., S. calocephala Boiss ,S. persica Boiss., S. leucactis Patzak. and S. brachycarpa Boiss.et Hoh. The study done by using Gas Chromatography Mass Spectrometry (GC-MS), the results helped in isolation species by distinguishing them with their own chemical compounds. All the studied species participated in a single chemical compound Oleic Acid, but the species varied in the number of chemical compounds. S. brachycarba contains (18) chemical compounds, S. leucactis contained (14) compounds, S. persica recorded (21) compounds and S. calocephala contained (28) compounds which was the highest among the studied species and the record (6) compounds in the S. palaestina, which was the lowest species. The species varied in distinguished compounds of each species, S. persica was distinguished by (4) chemical compounds S. brachycarba (3) distinct compounds while S. leucactis was characterized by (4) compounds, whereas S. calocephala (4) compounds and finally S. palaestina characterized by a single compound.Keywords: Scabiosa, Dipsacacea, Chemotaxonomy.